What Comes First - A Fact or a Topic? - Yusupova Nargiza Rakhmonbek Kizi; Shoyimov Abbos Glulomjon ug'li (International Journal on Integrated Education, 2022)
There are different approaches to the issue of "Which comes first - the fact or the topic?" This article discusses about the fact and the topic, understanding this problem, looking at it from different perspectives.